Risk of Intracranial Hemorrhage in Ground‐level Fall With Antiplatelet or Anticoagulant Agents. (5th June 2017) - Ganetsky, Michael; Lopez, Gregory; Coreanu, Tara; Novack, Victor; Horng, Steven; Shapiro, Nathan I.; Bauer, Kenneth A.
Abstract: Objectives: Anticoagulant and antiplatelet medications are known to increase the risk and severity of traumatic intracranial hemorrhage (tICH), even with minor head trauma. Most studies on bleeding propensity with head trauma are retrospective, are based on trauma registries, or include heterogeneous mechanisms of injury. The goal of this study was to determine the rate of tICH from only a common low‐acuity mechanism of injury, that of a ground‐level fall, in patients taking one or more of the following antiplatelet or anticoagulant medications: aspirin, warfarin, prasugrel, ticagrelor, dabigatran, rivaroxaban, apixaban, or enoxaparin. Methods: This was a prospective cohort study conducted at a Level I tertiary care trauma center of consecutive patients meeting the inclusion criteria of a ground‐level fall with head trauma as affirmed by the treating clinician, a computed tomography (CT) head obtained, and taking and one of the above antiplatelet or anticoagulants. Patients were identified prospectively through electronic screening with confirmatory chart review. Emergency department charts were abstracted without subsequent knowledge of the hospital course. Patients transferred with a known abnormal CT head were excluded. Primary outcome was rate of tICH on initial CT head. Rates with 95% confidence intervals (CIs) were compared. Results: Over 30 months, we enrolled 939 subjects. The mean ± SD age was 78.3 ± 11.9 years and 44.6% were male. There were a total of 33 patients with tICH (3.5%, 95% CI = 2.5%–4.9%). Antiplatelets had a rate of tICH of 4.3% (95% CI = 3.0%–6.2%) compared to anticoagulants with a rate of 1.7% (95% CI = 0.4%–4.5%). Aspirin without other agents had an tICH rate of 4.6% (95% CI = 3.2%–6.6%); of these, 81.5% were taking low‐dose 81 mg aspirin. Two patients received a craniotomy (one taking aspirin, one taking warfarin). There were four deaths (three taking aspirin, one taking warfarin). Most (72.7%) subjects with tICH were discharged home or to a rehabilitation facility. There were no tICH in 31 subjects taking a direct oral anticoagulant. CIs were overlapping for the groups. Conclusion: There is a low incidence of clinically significant tICH with a ground‐level fall in head trauma in patients taking an anticoagulant or antiplatelet medication. There was no statistical difference in rate of tICH between antiplatelet and anticoagulants, which is unanticipated and counterintuitive as most literature and teaching suggests a higher rate with anticoagulants. A larger data set is needed to determine if small differences between the groups exist.